Total and organic mercury, selenium and alpha-tocopherol in some deep-water fish species - Afonso, Claudia (2015)
BACKGROUND: Mercury is a well-known toxic element present in seafood. Nevertheless some antioxidants, like selenium, as an integral component of the enzyme glutathione peroxidase, and alpha-tocopherol having a protective role against it, are present as well. The purpose of this study was to evaluate the levels of total mercury (Hg-T), organic mercury (Hg-Org), Se and alpha-tocopherol in some adult deep-water fish species caught off Portuguese waters. RESULTS: Levels of Hg-T were above EU limits in 6% of Lophius spp. and Aphanopus carbo, 2% ofLepidorhombus spp. and 70% of Helicolenus dactylopterus. Hg-Org represented the major fraction (more than 84%) of Hg-T in all studied muscles. The selenium concentration in muscle was similar in all species (about 0.4 mg kg(-1) wet weight) and the highest level of alpha-tocopherol (70 mg kg(-1) wet weight) was found in Aphanopus carbo. CONCLUSION: The muscle of all species studied is a good source of selenium, but only can give a small contribution of alpha-tocopherol. Attending to the provisional tolerable weekly intake established by the WHO/FAO for methylmercury, it appears that the species studied should be consumed sparingly. (c) 2008 Society of Chemical Industry. - QCA III - PO MARE [22-05-01- FDR-0006]. - The authors thank the financial support from QCA III - PO MARE "Valorizacao e Inovacao em Produtos da Pesca - 22-05-01- FDR-0006 - Vigilancia, Seguran a e Qualidade Alimentar" project and to Dr Narcisa Bandarra, Vanessa Ferraria and Patricia Anacleto for the technical support in the determination of selenium and a-tocopherol. The authors also thank the scientists of the U-REMS of the INRB-IP/IPIMAR, who supplied the fish and gave advice on the biological parameters.